2016
DOI: 10.3847/1538-4357/834/1/46
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the Frequency of Free-Floating Planets From a Synthesis of Microlensing, Radial Velocity, and Direct Imaging Survey Results

Abstract: A microlensing survey by Sumi et al. (2011) exhibits an overabundance of short-timescale events (t E 2 days) relative to that expected from known stellar populations and a smooth power-law extrapolation down to the brown dwarf regime. This excess has been interpreted as a population of approximately Jupiter-mass objects that outnumber main-sequence stars by nearly twofold; however the microlensing data alone cannot distinguish between events due to wide-separation (a 10 AU) and free-floating planets. Assuming … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 88 publications
2
25
0
Order By: Relevance
“…However, the statistical significance of Sumi et al's results is largely based on three shortest-timescale events (t E < 1 days). As we mentioned above, one measurement is incorrect and the model by Clanton & Gaudi (2017) shows that the remaining two are statistically consistent with being wide-orbit planets. That model still cannot account for a small overabundance of events with timescales between 1-2 days (see Figures 4 and 5 from Clanton & Gaudi 2017), but the statistical significance of the remaining excess relative to the short-timescale events expected from stars and brown dwarfs is small.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, the statistical significance of Sumi et al's results is largely based on three shortest-timescale events (t E < 1 days). As we mentioned above, one measurement is incorrect and the model by Clanton & Gaudi (2017) shows that the remaining two are statistically consistent with being wide-orbit planets. That model still cannot account for a small overabundance of events with timescales between 1-2 days (see Figures 4 and 5 from Clanton & Gaudi 2017), but the statistical significance of the remaining excess relative to the short-timescale events expected from stars and brown dwarfs is small.…”
Section: Introductionmentioning
confidence: 80%
“…They found an excess of nine short 2 events, relative to what was expected from brown dwarfs and stars, and they attributed this excess to a large population of Jupiter-mass planets, which should be nearly twice as common as mainsequence stars. Clanton & Gaudi (2017) modeled the microlensing signal expected from exoplanets on wide orbits using constraints from microlensing, radial velocity, and direct imaging surveys and concluded that at most ∼ 40% of short-timescale events detected by Sumi et al (2011) can be interpreted as due to wide-orbit planets. However, the statistical significance of Sumi et al's results is largely based on three shortest-timescale events (t E < 1 days).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, stars can eject dust and gas and planetary debris after their time on the main sequence, and it is even possible that small bodies form directly in interstellar space. Although spacecraft, radar and visual detection arrays definitely observe streams of dust-sized interstellar micrometeorites Strub et al [2015], Baggaley [2000], and although there appears to be a population of nomadic interstellar planets Sumi et al [2011], Strigari et al [2012], Clanton and Gaudi [2017], until recently there was no firm evidence for even a single galactic asteroid or comet coming into the solar system from interstellar space Engelhardt et al [2017].…”
Section: Introductionmentioning
confidence: 99%
“…At the low-mass end, microlensing has detected several free-floating planet candidates based on their short microlens timescale, t E 2 days (Sumi et al 2011;Mróz et al 2017Mróz et al , 2018Mróz et al , 2019, including a few possible Earth-mass objects. Such discoveries are crucial for testing theories about the origin and evolution of free-floating planets (Veras & Raymond 2012;Pfyffer et al 2015;Ma et al 2016; Barclay et al 2017;Clanton & Gaudi 2017). For more massive objects (i.e., isolated brown dwarfs), five have been discovered by microlensing: OGLE-2007-BLG-224L (Gould et al 2009, OGLE-2015-BLG-1268L (Zhu et al 2016), OGLE-2015-BLG-1482 58 (Chung et al 2017), OGLE-2017-BLG-0896 (Shvartzvald et al 2019), and OGLE-2017-BLG-1186 59 (Li et al 2019).…”
Section: Introductionmentioning
confidence: 99%